STATISTICAL ANALYSIS OF TOURISM ACTIVITY (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article analyzes the current state of Uzbekistan's tourism potential, the country's strengths and weaknesses in the field of tourism, opportunities and threats through a SWOT analysis.Also, the existing problems in the tourism market and proposals for their elimination are presented. As a result of the analysis, directions such as improvement of transport infrastructure, improvement of service quality and development of domestic tourism were determined. The article suggests important strategies for developing sustainable tourism in Uzbekistan and integrating it into the international market.
Keywords: Uzbekistan, tourism potential, SWOT analysis, tourist routes, tourism infrastructure, service provision, domestic tourism, international tourism, tourism market growth, sustainable tourism, cultural tourism, marketing strategies.